PENDIDIKAN KEWARGANEGARAAN BERBASISKAN NILAI LOKAL : IDENTIFIKASI DAN IMPLEMENTASI - ., Winarno (PKn Progresif, 2008)
Civics Education as a subjet mater in Indonesia take a few funtions. This funtion are, as a value education, democrati politic education , citicenship education and nationality education. Civics Education as a value education include using value based approach. This value are Pancasila as nation noble values and local values. The approach is agree with use is inculcation approach. Therefore this approach is combinazed with  way or metod in another approach. This is nemed eclective approach.